Binary composite (TiO2-Gr) based nano-enhanced organic phase change material: Effect on thermophysical properties - Laghari, Imtiaz Ali; M., Samykano; A.K., Pandey; K., Kadirgama; Mishra, Yogeshwar Nath (2022)
The latent heat storage technology using Phase Change Materials (PCMs) has recently been extensively utilized in energy conservation and management to reduce energy consumption. To improve the thermal conductivity of PCMs, they have been incorporated with nanoparticles. In this article, we report, Titanium dioxide-Graphene (TiO2:Gr) binary composite (1 wt% TiO2: 0.1, 0.5, 1 and 2 wt% of Graphene (Gr)) with Paraffin wax (PW) to improve the thermophysical properties added with sodium dodecylbenzene sulphonate (SDBS) as surfactant. Ultraviolet-visible spectrometer (UV–VIS), Fourier transform infrared spectroscopy (FT-IR), Differential scanning calorimeter (DSC), Thermogravimetric analyzer (TGA), Field Emission Scanning Electron Microscopy (FESEM) and Thermal property analyzer (TEMPOS) were used for material characterizations. The latent heat capacity of the PW/Titanium oxide (TiO2) composite and the PW/TiO2-Gr binary composites were improved by 8.62% and 10.02%, respectively, in comparison to base PCM. The thermal conductivity of the composite PCMs with PW/TiO2-1.0 and PW/TiO2Gr-1.0 is 120% and 179% higher than base PW. The FT-IR spectra demonstrated no chemical interaction between the PW and the nanoparticles. TGA results presented improved thermal stability by integration of the TiO2-Graphene particles into the matrix of paraffin wax. The light transmission of the prepared composite was reduced by 58.30% related to base PW, resulted increased light absorption and, subsequently, enhanced photothermal conversion. The composite's improved thermal conductivity and enthalpy make it a strong contender for use in TES and solar photovoltaics thermal systems.